Synthesis and characterization of BaTi1−xNbxO3 ferroelectric perovskite oxides with tunable band gap, anomalous photovoltage, and enhanced energy storage - Mala D.; Singh C.B.; Singh A.K. (My University, 2025)
In this study, we investigated dense BaTi1−xNbxO3 ceramics prepared by the conventional solid-state reaction technique which shows energy storage properties and anomalous photovoltaic effect. Structural analysis of BaTi1−xNbxO3 compositions has been performed by fitting the XRD patterns with Rietveld method and all samples show coexisting tetragonal (P4 mm) and cubic (Pm-3 m) structures. Composition (x = 0.04) shows minimum band gap (2.4 eV), smaller than pure BaTiO3 ceramics which can be attributed to lattice distortion and oxygen vacancies. The improved breakdown strength and energy storage density is achieved for BaTi0.93Nb0.07O3 composition. This ferroelectric ceramic shows energy storage of 278.7 mJ/cm2 and high energy conversion efficiency (90.4%). The composition (x = 0.07) exhibit a very high photovoltage (26 V) under visible light wavelength. These findings provide a fresh approach to create high-performance functional ferroelectric materials for energy applications. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2024.